Exploring the opportunities of a balloon-satellite in Bangladesh for weather data collection and vegetative analysis - Rhaman, Md. Khalilur; Bin Shafique, Md. Ishraque; Halim, M.A. Razzaq; Rabbi, Fazle (© 2016 IOP Publishing, 2016)
This article was published in the IOP Conference Series: Earth and Environmental Science [©2016 Published by IOP Publishing Ltd.] and the definite version is available at: 10.1088/1755-1315/38/1/012009 The Article's website is at: http://iopscience.iop.org/journal/1755-1315